Histological changes to the rat mandibular condyle in response to long-term exposure to an extremely low frequency magnetic field - Tacir, Ibrahim H; Ulku, Sabiha Z; Ketani, Muzaffer A; Akdag, Mehmet Z (Makara Journal of Health Research, 2019)
Background: The need for electrical power continues to increase along with the rapidly growing economies of industrialized countries. However, the effects of electrical fields (EFs) on human health remain unclear. Hence, the aim of the present study is to evaluate the histological effects of an extremely low frequency magnetic field (ELF-MF) on the rat mandibular condyle. Methods: Twenty female Sprague–Dawley rats were randomly allocated to one of two groups (n = 10): an untreated control group and an ELF-MF group exposed to a 1.5-mT ELF-MF for 4 h per day for 6 months. After exposure, the left mandibular condyles of all rats were collected for histopathological examinations. Results: The histopathological changes to the ELF-MF group included a non-homogenous appearance and decreased thickness of the hypertrophic layer, irregular appearances of bone marrow cavities, significant deterioration, and delayed calcification and ossification. There were no significant differences in the thicknesses or histomorphometric appearances of the fibrotic, proliferative, and hypertrophic layers of the mandibular condyle of rats between the groups (p = 0.05). Conclusion: Long-term ELF-MF exposure can induce histopathological changes to the mandibular condyle of rats.